ISO/IEC 27005-Based E-Learning Risk Management with Blockchain Architecture: A Case Study of Semarang University - Irfan, Muhammad Nur; Ramadhania, Salwa; Hadi, Soiful; Pungkasanti, Prind Triajeng (Universitas Bina Darma, 2025)
This study aims to analyze information security risk management in the Semarang University E-Learning System using the ISO/IEC 27005 standard and to design a blockchain-based architecture as a conceptual strategy for improving data security. The implementation of blockchain in this study is limited only to the conceptual design stage, which serves as a risk mitigation framework without direct application to the system. The research method uses a Waterfall approach that includes the stages of risk identification, needs analysis, risk evaluation, adjustment through expert judgment, risk prioritization, and design of a blockchain-based mitigation architecture. Data were collected through quantitative surveys of students, lecturers, and system users, and qualitative assessments from information technology administrators. The analysis results show that the risks with very high priority are R005 with a score of 22.03 related to personal data security, and R007 with a score of 21.03 related to system access failure at critical times. The integration of blockchain in this design serves to improve data integrity, transaction process transparency, and service availability through distributed recording and smart contract-based automatic verification. This study provides novelty by simultaneously combining the ISO/IEC 27005 approach and blockchain architecture concepts in the context of a university e-learning system, resulting in a comprehensive strategic framework for information security risk management. The blockchain implementation in this study is limited to the conceptual design stage.